EL PRECERÁMICO EN QOTAMISA PAMPA - PUNAS DE HUANCAPI- VICTOR FAJARDO - AYACUCHO - Laurente Palomino, Sonia (2017)
This is based on the study of the archaeological site of Pampa Qotamisa from a systematic archaeological survey, taking into account the landscape surrounding the site. The aspect that has been considered in the study of these societies were the weapons used for hunting (Tips), the analysis of the wildlife that until today exists on the site and the landscape in which encounters between hunters and camelids are given are the indicators of these companies.Aims to characterize the landscapes where they were promoted and materialized encounters between hunters and camelidaes area Qotamisa Pampa, evaluating the different factors involved in this activity such as (hunters, landscape, camels, technology, etc.), these interrelate and converge in hunting scenarios. The choice of this area for activities responds that this has all the characteristics necessary for election as landscape for the occupation of territory by camelids, given certain characteristics such as the presence of water, grasslands, gentle slopes and high rocky . It is for this reason that Qotamisa Pampa is a case for research proposed here, so make a cursory investigation and evaluate the characteristics of the landscapes, the associated cultural material (lithic artifacts and paintings) and others, so it can be held in the approaches of Landscape Archaeology.